AUDITING FINANCIAL AND NON-FINANCIAL INFORMATION ON SUSTAINABILITY - VICTOR MUNTEANU; ADRIANA HORAICU; ALICE MARIANA PREDA (SIMION); ANA-MARIA COMÂNDARU (ANDREI) (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
Public interest entities as well as private companies have moved from voluntary reporting to mandatory reporting of financial and non-financial information on environmental, social and governance issues. Basically, new integrated reporting requirements appeared, applicable on January 1, 2017. It is time to find implications for financial audit and to apply assurance procedures to integrated reporting by using the revised ISAE 3000 Standard. To increase the credibility of these sustainability reports, auditors can perform assurance assignments that contribute to a better image of the company. Auditing financial statements and performance reports increases their value in terms of reporting on business conduct. The external safeguards provided in the Sustainability Report may increase the credibility of stakeholders with the information provided. This reduces the risk of misinformation about the environment and the use of reports as a simple public relations activity. Auditing sustainability reports presents different challenges than those found in auditing financial statements. This is also the reason why the International Auditing and Assurance Standards Board (IAASB) has published a consultation paper on the provision of insurance for extended external reporting [1]. According to the revised ISAE 3000, in a limited insurance mission (review mission), “the practitioner’s conclusion is expressed in a form that conveys the message that, based on the procedures applied, nothing has attracted the practitioner’s attention so that he or she believes that the information in question is significantly distorted ”. In such cases, the risk of the mission is reduced to an acceptable low level in the circumstances of the mission, but the risk is higher than in the case of a reasonable assurance mission [2]..In this context, taking into account the need to audit financial and non-financial information, in this scientific approach we will conduct a study on auditing information from the annual report of a Romanian company and present an analysis of the results, following the audit, on achieving the level of development of sustainability